Development of high-performance electric motors for electric and hybrid vehicles - Fong, Elvi Yun Long (Nanyang Technological University, 2024)
The world is moving towards sustainable transportation solutions, and electric and hybrid vehicles (EVs and HEVs) are at the forefront of this shift. The Permanent Magnet Brushless DC (PMBLDC) motor is a crucial component in this transition, offering several advantages such as high efficiency, low noise, compact size, reliability, and low maintenance requirements. Electric drives are also essential for EVs and HEVs. However, integrating them requires a convergence of various power electronic technologies such as converter topologies, microprocessor systems, switching devices, and control strategies. Designing a single drive solution that can accommodate different vehicle types is a significant challenge. This project aims to address this challenge by designing and producing high performance permanent magnet motors for use in electromobility applications such as EVs, bikes, and aircraft. These motors are engineered to deliver superior performance attributes such as high efficiency levels, elevated power density, and robust fault tolerance capabilities. The study includes exhaustive investigations into the electromagnetic, structural, and thermal aspects of the motors with a particular emphasis on determining the fundamental determinants influencing power density, efficiency, and fault-tolerant capabilities.